2015
DOI: 10.3171/2014.12.peds14462
|View full text |Cite
|
Sign up to set email alerts
|

Case report of an epidural cervical Onchocerca lupi infection in a 13-year-old boy

Abstract: A 13-year-old boy presented with fever and neck pain and stiffness, which was initially misdiagnosed as culture-negative meningitis. Magnetic resonance images of the brain and cervical spine demonstrated what appeared to be an intradural extramedullary mass at the C1–3 level, resulting in moderate cord compression, and a Chiari Type I malformation. The patient underwent a suboccipital craniectomy and a C1–3 laminectomy with intradural exploration for excisional biopsy and resection. The lesion containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
1
Order By: Relevance
“…The importance of O. lupi lies not only in its ability to produce potentially blinding disease in dogs, but also in its role as a zoonotic agent and as a potential animal model for O. volvulus . A better understanding of the life cycle of O. lupi , as well as treatment and prevention strategies, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of O. lupi lies not only in its ability to produce potentially blinding disease in dogs, but also in its role as a zoonotic agent and as a potential animal model for O. volvulus . A better understanding of the life cycle of O. lupi , as well as treatment and prevention strategies, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Human cases of infection with O. lupi nematodes have been reported Old World countries, including Albania, Crimea, Iran, Tunisia, and Turkey ( 3 , 8 11 ). All case-patients had ocular disease caused by subconjunctival nodules containing nematodes.…”
mentioning
confidence: 99%
“…In the present study, one of the O. lupi infected dogs showed neurological abnormalities, although previous studies have not reported this clinical sign in dogs positive to O. lupi . However, this condition was described in a 13-year-old boy presenting neurological signs due to aberrant epidural cervical infection, in the spinal canal, by adult nematodes [ 19 ]. However, since an aberrant laryngeal location of O. lupi was previously reported in a dog from Portugal [19], the dog with neurological signs is referred to as (dog 1, Table 1 ) and one without those signs as (dog 4, Table 1 ), were subjected to imaging tests to detect the presence of adults or nodules containing O. lupi adults.…”
Section: Resultsmentioning
confidence: 99%